2010
DOI: 10.1074/jbc.m110.141556
|View full text |Cite
|
Sign up to set email alerts
|

CD23 Sheddase A Disintegrin and Metalloproteinase 10 (ADAM10) Is Also Required for CD23 Sorting into B Cell-derived Exosomes

Abstract: The low affinity receptor for IgE, CD23, is the natural regulator of IgE synthesis, and understanding both the synthesis and the catabolism of CD23 are, thus, important issues. Membrane CD23 is cleaved by a disintegrin and metalloproteinase 10 (ADAM10) and this cleavage influences the ability of CD23 to regulate IgE. In contrast to the belief that cleavage is a cell surface event, endosomal neutralization with NH 4 Cl was found to dramatically reduce CD23 cleavage, suggesting that the majority of CD23 cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 49 publications
4
51
0
3
Order By: Relevance
“…The low levels of lysosomal proteases present in B cells may assure that the antigen is poorly degraded during the sorting process into secreted vesicles. Second, the low affinity receptor for IgE (CD23) found in B cell-derived vesicles [65] could mediate IgE-immune complex binding for shuttling antigen to other APC.…”
Section: Functional Comparison Of B Cell-and Dc-derived Vesiclesmentioning
confidence: 99%
“…The low levels of lysosomal proteases present in B cells may assure that the antigen is poorly degraded during the sorting process into secreted vesicles. Second, the low affinity receptor for IgE (CD23) found in B cell-derived vesicles [65] could mediate IgE-immune complex binding for shuttling antigen to other APC.…”
Section: Functional Comparison Of B Cell-and Dc-derived Vesiclesmentioning
confidence: 99%
“…Khokha and colleagues (Shimoda et al 2014) recently demonstrated that fibroblasts engineered to be deficient for all four Timp genes functionally recapitulate cancer-associated fibroblasts (CAFs) and activate oncogenic signaling in cancer cells through ADAM10-rich exosomes, which lead to increased cancer cell motility. Finally, proteolysis has also been shown to occur within exosomes in the case of ADAM10, which rapidly cleaves the immunoglobulin E (IgE) receptor CD23 prior to its release from B cells (Mathews et al 2010).…”
Section: Exosomes As a Means To Regulate And Transfer Proteases Betwementioning
confidence: 99%
“…ADAM10, effective in site 2 cleavage in Notch1 and 2 signaling, and is important for T cell and marginal zone B cell development [15; 19; 24]. Several papers have shown ADAM10 to regulate B cell Ig production, including its role as the primary sheddase of CD23, a negative regulator of IgE production [17; 19; 23; 26]. Important to our work, Mathews et al showed that B cell-restricted ADAM10 deficiency decreased antigen-specific IgE, eosinophila and IL-5 production in an IgE/mast cell-dependent airway hyperresponsiveness (AHR) model [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, ADAM10 cleaves many substrates involved in immunity, including Notch 1, Notch 2, DL1, CD23, TNF, and IL-6R [14; 16; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26]. ADAM10-dependent Notch signaling has been demonstrated in recent years to be crucially important for the proper differentiation and distribution of T cells and B cells [17; 19; 24].…”
Section: Introductionmentioning
confidence: 99%